Trading Identities: The Souvenir in Native North American Art from the Northeast, 1700-1900 - Phillips, Ruth B. (Ruth Bliss) (McGill-Queen's University Press, 1998)
Indians in northeastern North America produced a variety of art objects for sale to travelers and tourists during the 18th and 19th centuries. This art is of high quality and great aesthetic interest, but has been largely ignored by scholars. This study combines fieldwork, art historical analysis
Section: xvii, 334 pages : illustrations (certaines en couleur)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Sensible Objects: Colonialism, Museums, and Material Culture - Edwards, Elizabeth; Gosden, Chris; Phillips, Ruth B. (Routledge, Taylor & Francis Group, 2020)
Anthropologists of the senses have long argued that cultures differ in their sensory registers. This groundbreaking volume applies this idea to material culture and the social practices that endow objects with meanings in both colonial and postcolonial relationships. It challenges the privileged position of the sense of vision in the analysis of material culture. Contributors argue that vision can only be understood in relation to the other senses. In this they present another challenge to the assumed western five-sense model, and show how our understanding of material culture in both historical and contemporary contexts might be reconfigured if we consider the role of smell, taste, touch and sound, as well as sight, in making meanings about objects.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; _Nettoyé